Network culture as the foundation of national security and social development - Bankovskaya, Yuliya L. (Human in the Socio-Cultural Dimension, 2025)
It is substantiated that network culture is an adaptive strategy that allows states to effectively counter threats and challenges of the 21st century, maintaining the security of the development of the individual and the state. It is indicated that network culture does not simply complement the value-normative standards operating in offline reality, but creates a fundamentally new form of interaction between people, forming relevant opportunities for intercultural dialogue. The factors of digital interconnections and interactions of users are determined. The political and legal aspects of national security are outlined. The specific features of the state cultural policy in the field of network technologies are indicated.